Pre-Service Science Teachers in International Teaching Practicum: Reflection of the Experience - Ahmad, N. J.; Ishak, N. A.; Samsudin, M. A.; Meylani, V.; M. Said, H. (Jurnal Pendidikan IPA Indonesia, 2019)
International Teaching Practicum (ITP) is a platform that provides experiences and opportunities for pre-service teachers to grow both personally and professionally in the teaching profession. This study reported the outcomes of an eighth-week ITP Program in Brunei and Indonesian’s schools for Malaysian undergraduate secondary pre-service teachers in four aspects; namely: (1) teaching strategy in science education; (2) communication skills and confidence in teaching science; (3) perspective in science education and culture; and (4) interpersonal skills in teaching science. All of the pre-service teachers shared their experiences in their weekly reflective journals and the data from the structured interviews during ITP. The findings indicated that the pre-service teachers were more creative and innovative in applying various approaches in teaching science as they must improvise the learning resources to suit the teaching context. The pre-service teachers were found to be more confident, and they experienced substantial development in their communication skills. Their views on education and culture of science also have shifted, and these attributes also have enhanced their interpersonal skills that provide opportunities for more networking and linkages with the host schools. The implication of these findings is believed to link to their belief in enhancing their professional experiences that contribute to the science teaching profession.